2011
DOI: 10.1007/s11133-011-9203-3
|View full text |Cite
|
Sign up to set email alerts
|

Tort Reform and Access to Justice: How Legal Environments Shape Lawyers’ Case Selection

Abstract: How do lawyers decide which cases to accept? Previous studies suggest that they use a simple risk/return formula to make such decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…First, it expands our knowledge of sociocultural constraints on economic incentives in the practice of law. Previous research has identified a list of factors that mediate law practitioners' profit seeking behavior, including professionalism (Kritzer 1984), ideological commitments (Menkel-Meadow and Meadow 1983;Sandefur 2007), reputational concerns (Daniels and Martin 1999;Kim 2009a;Johnson Jr.1980-81;Kritzer 1998), legal environments (Trautner 2011), and geographic markets (Daniels and Martin 1999;Van Hoy 1999). This study builds on and extends this line of inquiry by adding a new parameter to this list, namely, relational embeddedness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it expands our knowledge of sociocultural constraints on economic incentives in the practice of law. Previous research has identified a list of factors that mediate law practitioners' profit seeking behavior, including professionalism (Kritzer 1984), ideological commitments (Menkel-Meadow and Meadow 1983;Sandefur 2007), reputational concerns (Daniels and Martin 1999;Kim 2009a;Johnson Jr.1980-81;Kritzer 1998), legal environments (Trautner 2011), and geographic markets (Daniels and Martin 1999;Van Hoy 1999). This study builds on and extends this line of inquiry by adding a new parameter to this list, namely, relational embeddedness.…”
Section: Discussionmentioning
confidence: 99%
“…Economic incentives, however, are rarely unbounded in legal practice. Rather, they are often mediated by sociocultural factors, such as lawyers' sense of responsibility, reputational concerns, desire for professional challenges, political ideologies, and so on (Daniels and Martin 1999;Kim 2009a;Kritzer and Krishnan 1999;Menkel-Meadow and Meadow 1983;Van Hoy 1995Trautner 2011).…”
Section: Ke LImentioning
confidence: 99%
“…For example, Kritzer (1997) found that plaintiffs' lawyers routinely turn away more than half those seeking representation, but some plaintiffs' lawyers are far more selective. Trautner (200622007), Parikh (2001), and Hyman et al ( , 2017 also find strong evidence of screening. Huycke and Huycke (1994) surveyed individuals who contacted plaintiffs' attorneys seeking representation in med mal cases, and found that only 3.3 percent of these contacts resulted in the filing of a lawsuit.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Thus, like other professionals who control people's access to socially valued resources, plaintiffs' lawyers act as 'gate-keepers' to justice." More recently, Trautner (2011) argued that "because people injured by defective products or medical errors almost always need a lawyer in order to obtain compensation in the civil justice system, lawyers' decisions determine who has the opportunity to be NOTES: Summary statistics for Illinois med mal cases closed over 2000-2010, by nature of representation. First-tier firms are the top 5 percent of Active Firms by total recovery; second-tier firms are the 90 firms that are the next 20 percent of Active Firms; third-tier firms are the remaining 75 percent of Active Firms, based on total amount recovered.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation